Simulations of employment for individuals in LIMTCP consumption-poor households in Tanzania and Ghana, 2012 - Thomas Masterson; Kijong Kim; Fernando Rios-Avila (Levy Economics Institute of Bard College, 2016)
New methodology for producing employment microsimulations is introduced, with a focus on farms and household nonfarm enterprises. Previous simulations have not dealt with the issue of reduced production in farm and nonfarm household enterprises when household members are placed in paid employment. In this paper, we present a method for addressing the trade-off between paid employment and the farm and nonfarm business activities individuals may already be engaged in. The implementation of the simulations for Ghana and Tanzania is described and the quality of the simulation results is assessed.
Keywords: C14; C40; D31; J22; 330; LIMTCP; Microsimulation; Ghana; Tanzania; Employment; Unpaid Family Labor; Household Production; Time Use